User Experience V-QITA : Nursing Education for Nursing Students - Suci Noor Hayati; Eva Supriatin; Tri Antika Rizki Kusuma Putri; Masdum Ibrahim; Diwa Agus Sudrajat; Sainah; Roselina Tambunan (STIKep PPNI Jawa Barat, 2022)
Aims : The development of science and technology encourages the learning process to be more applicable and interesting as an effort to improve the quality of education. The use of edugame as an evaluation of learning by students is the right solution. The purpose of the study was to identify student experiences in using V-Qita Edugame in patient safety learning. Designs:This research is a quantitative research using descriptive method through a cross-sectional approach. Methods:The population in this study were 60 students of STIKep PPNI West Java. The sampling technique used is purposive sampling with random sampling. Collecting data using a user experience questionnaire (UEQ). The questionnaire was adapted from the research of Laugwitz et al. This questionnaire contains 26 items that represent the 6 factors that will be analyzed to evaluate the user experience, namely attractiveness, efficiency, perspicuity, dependability, stimulation, and novelty. Results : The five user experience subvariables show an average value close to the maximum value so that it is stated that the user's response is positive to the use of edugame as a form of evaluation in patient safety learning. Stimulation is an experiential subvariable that emphasizes that users find edugames fun and motivating. Conclusions:The students' experience in using V-Qita Edugame is at an average value of 4.62, meaning that the student response in using Edugame as a positive learning evaluation. Stimulus got the highest value compared to other subvariables. experiences that emphasize users find SAP enjoyable and motivate users to use it.